Program Diorama Kearsipan Sebagai Sarana Literasi Budaya Pemustaka Di Aceh - Niswana Almadania; Nurhayati Ali Hasan; T. Mulkan Safri; Abdul Manan; Mukhtaruddin Mukhtaruddin (Tik Ilmeu: Jurnal Ilmu Perpustakaan dan Informasi)
Indonesia has a rich cultural diversity, including Aceh, which is known for its history and traditions. However, globalization and modernization have led to cultural shifts, especially among the younger generation, who are increasingly exposed to new values. Libraries play a crucial role in cultural preservation, one of which is through the archival diorama at the Aceh Library and Archives Office, which integrates archives, art, and technology to enhance cultural literacy. This study employs a qualitative research method using interviews, observations, and documentation techniques. The findings indicate that the archival diorama is effective in improving cultural and historical literacy in Aceh. However, challenges such as the lack of descriptions in archival visualizations and limited individual access remain. Therefore, it is recommended to enhance information presentation, incorporate interactive technology, and expand promotional efforts to increase public engagement with the diorama.